Strengthening international exchange and cooperation with labor unions in America in the field of apprenticeship/vocational training : A case study on apprenticeship/vocational education and training in the US States of Wisconsin, New York and South Carolina ; Country report - Nehls, Hermann [Verfasser] (bfw-Berufsfortbildungswerk, 2019)
"The Unions4VET project has been promoting international cooperation between labor unions in the field of vocational training since 2015. The aim of the project is to improve the quality of vocational training and to strengthen the role of trade unions in the governance of vocational training through the transnational exchange of knowledge, experience and good practice. Since the beginning of the project, meetings, workshops, conferences and projects with partner labor unions from Costa Rica, Greece, Italy, Latvia, Portugal, Slovakia, and the USA have been organised. In the next three years, the international labor union network will be deepened and expanded to other partner countries. The basis for cooperation with the partner labor unions is in each case an analysis of the vocational training policy situation and challenges in the partner countries from a labor union perspective. This report on the vocational education and training system in the USA is based on secondary analyses and numerous expert interviews with US vocational education and training stakeholders and was prepared in 2019." (Autorenreferat ; BIBB-Doku)
Keywords: S 3.5.4.1 Gewerkschaften; I 1 Internationale Berufsbildung; S 2.3 Berufsbildungspolitik; S 2.3.2 Programme in der Berufsbildung; Gewerkschaft; Internationale Zusammenarbeit; Berufsbildungspolitik; Sekundäranalyse; USA